Digital Marketing Strategies And Their Effect On Consumer Behaviour Toward Electronic Products On Amazon - Thiyagarajan, N.; Sasikumar, P. (Journal of Neonatal Surgery, 2025)
The fast evolution of digital marketing has significantly reshaped consumer purchasing behaviour, mainly in the amazonplatform. This study examines the factorssuch as Content Quality and Relevance, User Experience, Email Marketing, Price Transparency, Brand Trust, Transparencyand their influence on Customer Engagement toward electronic products on Amazon. The Amazon platform's sophisticated algorithm-driven marketing tools and customer-centric interface make it a prime environment to analyse how digital promotions affect buying decisions, (Miklosik, et al., 2015).In today’s competitive digital marketplace, understanding the psychological triggers behind consumer engagement is essential. This studyindicates how customer reviews, targeted advertising, product recommendations,star ratings, and dynamic pricing influence consumer trust and perceived value. The study also observes the influence of CQ and Ron Brand Trust and Transparencytoward specific electronic brands. The research discloses patterns in consumer response to marketing stimuli.The findings of this study emphasize the importance of integrating data-driven marketing strategies with consumer behaviour insights to drive conversions, raise engagement, and enhance brand trust on digital platforms like Amazon